Bacteriological profile and frequency of antibiotic resistance in the infected diabetic foot: Bacteriological profile in the infected diabetic foot - Fetni, Samira; Ouahab, Ammar; Hamlaoui, Fatma (Cellular and Molecular Biology, 2023)
The diabetic foot (DF) is a major public health problem, with infection of the DF being a major risk factor for amputation. This study aimed to establish the bacteriological profile of diabetic foot infection and to evaluate the resistance of isolated bacteria to antibiotics. Retrospective study of 150 patients in the internal medicine departments of the University Hospital of Batna, the University Hospital of Constantine and the EPH of Oum El Bouaghi, over 24 months from September 2019 to August 2021. The population had an average age of 46±13 years and a sex ratio of 1.88 in favour of men. The majority of patients were type 2 diabetics with a mean duration of the evolution of 20 years. The starting point of the foot lesions was inter-toe intertrigo and trauma. The most frequent lesion found was an infectious lesion followed by gangrene, classified in 33.64% of cases as Grade 2 according to Wagner. We performed a swab of the ulcer, and direct examination showed a predominance of Gram-negative bacilli (GNB) in 78.56% of the samples, 17 different bacterial species were isolated, predominantly Escherichia coli and Pseudomenas aeruginosa. We studied the antibiotic resistance of the most frequently isolated bacteria, the antibiotic therapy was initially probabilistic and then adapted to the antibiogram. The multidisciplinary management of diabetic foot is still very precarious, and the best treatment is prevention.